METHODOLOGY FOR REDUCING STUTTERING BASED ON ART THERAPY AND RELAXATION EXERCISES - Abdullayeva Karomat Islom qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article explores a methodology for reducing stuttering in children through the use of art therapy and relaxation exercises. The study examines how creative activities, such as drawing, painting, and modeling, combined with breathing and relaxation techniques, can positively influence speech fluency, decrease anxiety, and improve emotional stability. The effectiveness of these integrative approaches in supporting speech development and increasing motivation during therapy is analyzed. The results highlight that combining art therapy with relaxation exercises creates a supportive environment that enhances children’s confidence, reduces stress, and facilitates smoother speech production.